REINFORCEMENT IN DENTURE BASE RESINS- A REVIEW - A.S., Pavithra; Somasundaram, Jayalakshmi; A.K., Anjali (International Journal of Psychosocial Rehabilitation, 2020)
Polymethylmethacrylate is the most commonly used base material for dentures due to its excellent esthetics, ease of processing and repair, and economy. But it also has certain drawbacks, such as residual monomer allergy, poor mechanical strength , low strength, fragility, poor heat resistance, high thermal expansion coefficient, thermal shrinkage, etc. To overcome this disadvantage, many studies have shown that reinforcement or the addition of certain materials like fibers, glass, and fillers may improve their physical and chemical properties. The fracture resistance of polymethyl methacrylate (PMMA), the most popular denture base material, is not satisfactory. The mechanism of denture fracture is implied by flexural fatigue and impact fracture. The transverse strength of the base materials of the denture can, therefore, be an important indicator of their performance. Acrylic resin dentures are susceptible to fracture after clinical use, which is a problem of concern in prosthodontics. Impact failure outside the mouth and flexure fatigue failure in the mouth are the two most important causes of fracture of the denture base. This reinforcement can be done to get desired properties in denture base resins for stability . This review is based on reinforcements that can be done to denture base material to increase its physical and chemical properties. The relevant articles were collected from the period of 2000 to 2020 (till date), analyzed, and reviewed.This reinforcement can be done to get desired properties in denture base resins for stability .